(untitled) (Journal of Health Sciences, 2019)
Introduction: Even if the prevalence of intestinal parasites is high in Ethiopia, we still use only direct wet mount method for laboratory diagnosis of intestinal parasitic infections, having low sensitivity, and this significantly increases false-negative results. Therefore, the performance evaluation of three laboratory diagnostic methods is mandatory. Methods: Single stool sample was collected from March 2018 to June 2018, among 211 school children, and processed using a wet mount, modified Baermann (MB), and Ritchie’s methods. The sensitivity and negative predictive values (NPVs) at 95% confidence interval and Kappa values were calculated in terms of the gold standard method (the combined result of altogether). Results: The overall prevalence of intestinal parasites was 60.2%. The sensitivity and NPVs of the wet mount, MB, and Ritchie’s methods against the “Gold standard” test were 49.6% and 56.8%, 80.3% and 77.1%, and 67.7% and 68.8%, respectively. Conclusions: MB showed the best, and wet mount showed the least performance for the laboratory diagnosis of intestinal parasitic infections.